Evaluation of Quality Indicators with Lean Six Sigma In Pre and Post Analytical Laboratories - Nurhadi, Muhammad Ihsan; Ridwanna, Surya; Rinaldi, Sonny Feisal; Nurhayati, Betty (Mukhtabar Journal of Medical Laboratory Technology, 2025)
Background & Objective: Medical laboratories have an important role of 60-70% in diagnosis, patient monitoring, and prevention and treatment of diseases. Therefore, the laboratory must maintain and ensure the quality of service process. This study aims to determine the sigma value and identify waste in pre and post analytical in the laboratory, as well as determine Improvement proposals in order to reduce errors pre and post analytical laboratory. Method: This research design is descriptive study that Analyzes the process and quality indicators at pre and post analytical with the Lean Six Sigma approach, which is a combination of Lean methods that focus on eliminating waste and Six Sigma that focuses on eliminating defects. This research was conducted as a process Improvement effort with five Six Sigma work steps (DMAIC) and identified eight types of waste (DOWNTIME). Result: The results showed that the sigma value at pre and post analytical was 4.6 and 3.5 Sigma, and total sigma value for pre-post analytical was 4.3 Sigma so that both had not met the minimum target achievement of 5 Sigma (Excellent). There are two quality indicators that require improvement and enhancement including suitability of sample and TAT. The results also show that there are 4 wastes, consisting of 1 Defects, 1 Waiting, and 2 Not Utilizing Employees Knowledge. Conclusion: Proposed Improvements are then given so that all waste identified in this study can be minimized so that the achievement of sigma quality indicators can increase.